2018
DOI: 10.1090/jams/913
|View full text |Cite
|
Sign up to set email alerts
|

Exponential self-similar mixing by incompressible flows

Abstract: We study the problem of the optimal mixing of a passive scalar under the action of an incompressible flow in two space dimensions. The scalar solves the continuity equation with a divergence-free velocity field, which satisfies a bound in the Sobolev space W s,p , where s ≥ 0 and 1 ≤ p ≤ ∞. The mixing properties are given in terms of a characteristic length scale, called the mixing scale. We consider two notions of mixing scale, one functional, expressed in terms of the homogeneous Sobolev normḢ −1 , the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
140
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(140 citation statements)
references
References 46 publications
0
140
0
Order By: Relevance
“…There have been numerous recent contributions to this field: without any aim of completeness, we mention the works on lower bounds on mixing rates [30,39,43], mixing and regularity [15,31,52], and, more relevant for our discussion, quantification of mixing rates in passive scalars [1,10,22,53] (see also [2,4,38,44] and references therein for a dynamical system viewpoint) and two-dimensional Euler equations linearized around shear flows [27, 49-51, 54, 55] and vortices [6,19,56].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous recent contributions to this field: without any aim of completeness, we mention the works on lower bounds on mixing rates [30,39,43], mixing and regularity [15,31,52], and, more relevant for our discussion, quantification of mixing rates in passive scalars [1,10,22,53] (see also [2,4,38,44] and references therein for a dynamical system viewpoint) and two-dimensional Euler equations linearized around shear flows [27, 49-51, 54, 55] and vortices [6,19,56].…”
Section: Introductionmentioning
confidence: 99%
“…2 ), as well as (A) in the affirmative for p ≥ 3+ and the geometric mixing scale only. (Additionally, [2] proves exponential mixing for all p ≥ 1 and some special initial data ρ(·, 0).) In this paper we answer…”
Section: Introductionmentioning
confidence: 82%
“…To see the latter, we note that (30) in [26] shows for mean-zero functions equivalence of theḢ −1/2 -norm and the mix-norm 3. OtherḢ −s -norms of f have been used to quantify mixing, particularly theḢ −1 -norm [2,21,23,25,31], with the functional mixing scale being f Ḣ−1 f −1 ∞ (Wasserstein distance of f + and f − has also been used [6,29,31,32]). The latter may sometimes be more convenient than theḢ −1/2 -norm and also is directly related to mixing-enhanced diffusion rates when diffusion is present [9,11], but it lacks the useful connection to the mix-norm.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, fluid mixing attracted a remarkable attention by the mathematical fluid dynamics communities and beyond. The majority of the rigorous works, however, addressed the purely advective model, for instance, with a focus on absolute lower bounds on mixing rates [8,17,18,24,13], optimal mixing strategies [17,18,1,2,28], or universal mixers [11]. In the diffusive setting, it was shown that mixing flows enhance diffusive relaxation [6,4,7], while diffusion itself slows down the mixing rates [19].…”
Section: Physical Interpretationmentioning
confidence: 99%